Form and Function of Clostridium thermocellum Biofilms - Dumitrache, Alexandru (American Society for Microbiology, 2013)
The importance of bacterial adherence has been acknowledged in microbial lignocellulose conversion studies; however, few reports have described the function and structure of biofilms supported by cellulosic substrates. We investigated the organization, dynamic formation, and carbon flow associated with biofilms of the obligately anaerobic cellulolytic bacterium Clostridium thermocellum 27405. Using noninvasive, in situ fluorescence imaging, we showed biofilms capable of near complete substrate conversion with a characteristic monolayered cell structure without an extracellular polymeric matrix typically seen in biofilms. Cell division at the interface and terminal endospores appeared throughout all stages of biofilm growth. Using continuous-flow reactors with a rate of dilution (2 h(−1)) 12-fold higher than the bacterium's maximum growth rate, we compared biofilm activity under low (44 g/liter) and high (202 g/liter) initial cellulose loading. The average hydrolysis rate was over 3-fold higher in the latter case, while the proportions of oligomeric cellulose hydrolysis products lost from the biofilm were 13.7% and 29.1% of the total substrate carbon hydrolyzed, respectively. Fermentative catabolism was comparable between the two cellulose loadings, with ca. 4% of metabolized sugar carbon being utilized for cell production, while 75.4% and 66.7% of the two cellulose loadings, respectively, were converted to primary carbon metabolites (ethanol, acetic acid, lactic acid, carbon dioxide). However, there was a notable difference in the ethanol-to-acetic acid ratio (g/g), measured to be 0.91 for the low cellulose loading and 0.41 for the high cellulose loading. The results suggest that substrate availability for cell attachment rather than biofilm colonization rates govern the efficiency of cellulose conversion.